Spices technologies for maximum nutraceutical, environmental and social benefits - Prasath, D; Srinivasan, V; Rema, J; Singh, A K (Indian Horticulture, 2022)
Spices are high value and low volume, export-oriented commodities, commonly used for flavouring and seasoning of food and beverages. India is the world’s largest producer, consumer, and exporter of spices; the country produces about 75 of the 109 varieties listed by the International Organization for Standardization (ISO) and accounts for half of the global trading in spices. The consumption of spices is growing in the country with increase in purchasing power. It is envisaged that everyone in India would be consuming one spice or the other with a high per capita consumption. This may increase further due to rapid urbanization which needs spices as natural food preservatives. Growing demand from the emerging segment of nutraceuticals is driving the global consumption of Indian spices further at a time when the country is straining to meet the needs of the traditional food sector. Though spices contains diverse array of phytochemicals, the nutraceutical preparation often revolve around few major bioactive metabolites. Non-traditional use of spices including nutraceuticals now accounts for nearly 15% of spice production in India, estimated at 50 lakh tonne a year.